Persistent influence of obliquity on ice age terminations since the Middle Pleistocene transition - Bajo, Petra; Drysdale, Russell N.; Woodhead, Jon D.; Hellstrom, John C.; Hodell, David; Ferretti, Patrizia; Voelker, Antje H. L.; Zanchetta, Giovanni; Rodrigues, Teresa; Wolff, Eric; Tyler, Jonathan; Frisia, Silvia; et al. (Science (American Association for the Advancement of Science), 2020)
Understanding more exactly how the timing of deglaciations depends on changes in insolation, or the energy received by Earth from the Sun, requires precise and independent records of both environmental change and solar energy input. Bajo et al . strengthened the weak link of that two-member chain, the environmental record, by developing a precise, radiometrically dated chronology of the 11 deglaciations of the past million years derived from speleothems. This allowed them to show more clearly how the initiation and duration of glacial terminations over that period depended on solar obliquity and precession. Science , this issue p. 1235 Precisely dated speleothem records of deglaciations allow more insight into the role of insolation. Radiometric dating of glacial terminations over the past 640,000 years suggests pacing by Earth’s climatic precession, with each glacial-interglacial period spanning four or five cycles of ~20,000 years. However, the lack of firm age estimates for older Pleistocene terminations confounds attempts to test the persistence of precession forcing. We combine an Italian speleothem record anchored by a uranium-lead chronology with North Atlantic ocean data to show that the first two deglaciations of the so-called 100,000-year world are separated by two obliquity cycles, with each termination starting at the same high phase of obliquity, but at opposing phases of precession. An assessment of 11 radiometrically dated terminations spanning the past million years suggests that obliquity exerted a persistent influence on not only their initiation but also their duration.